Omaha, Neb., Rev. Ordinances ch. 42 § 10 (1890) - (:unkn) unknown (My University, 1890)
Prohibited the carrying of a concealed pistol or revolver, colt, billy, slungshot, brass knuckles or knuckles of lead, dirk, dagger, or any knife resembling a Bowie knife, or any other dangerous or deadly weapon. Punishable by fine up to $100.
Keywords: CARRY - CONCEALED